In vivo monitoring of arterially transplanted bone marrow mononuclear cells in a rat transient focal brain ischemia model using magnetic resonance imaging. (1st July 2013) - Kamiya, Nobuo; Ueda, Masayuki; Igarashi, Hironaka; Nishiyama, Yasuhiro; Suda, Satoshi; Okubo, Seiji; Inaba, Toshiki; Katayama, Yasuo
Abstract : Objectives: Intra-arterial transplantation of bone marrow mononuclear cells (BMMCs) effectively improves neuronal function and limits the infarct size. We monitored the fate of BMMCs labeled with super paramagnetic iron oxide (SPIO) until 7 days after the transplantation using high-field magnetic resonance imaging (MRI). Methods: Male Sprague-Dawley rats were subjected to 90-minute focal ischemia using the intraluminal suture technique followed by transplantation of 1×10 7 BMMCs or vehicle only via the ipsilateral carotid artery immediately after reperfusion. Autologous BMMCs were labeled with SPIO by electroporation prior to ischemia. MRI studies were performed at 1 hour, 24 hours, 3 days, and 7 days after reperfusion on each rat. The total infarct volume and the volume of negative dots were measured on T2-weighted images and T2*-weighted images, respectively. Results: One hour after BMMC transplantation, we confirmed wide spread distribution of BMMCs in the ischemic hemisphere as a negative dot. The volume of negative dot normalized by hemispheric volume decreased rapidly and was seldom seen at the seventh day after transplantation. The infarct volume was significantly smaller in the transplanted group than the vehicle group at 24 hours and 7 days after reperfusion. Discussion: The present study established In vivo monitoring of intra-arterial transplanted SPIO-labeled BMMCs immediately after reperfusion using MRI of a rat transient focal ischemia model. The accumulation of BMMCs in ischemic lesion at the acute stage of ischemia can be part of the conditions to limit the infarct size.